Copper binding and reactivity at the histidine brace motif: insights from mutational analysis of the Pseudomonas fluorescens copper chaperone CopC. Issue 12 (14th May 2021) - Ipsen, Johan Ø.; Hernández‐Rollán, Cristina; Muderspach, Sebastian J.; Brander, Søren; Bertelsen, Andreas B.; Jensen, Poul Erik; Nørholm, Morten H. H.; Lo Leggio, Leila; Johansen, Katja S.
Abstract : The histidine brace (His‐brace) is a copper‐binding motif that is associated with both oxidative enzymes and proteinaceous copper chaperones. Here, we used biochemical and structural methods to characterize mutants of a His‐brace‐containing copper chaperone from Pseudomonas fluorescens (PfCopC). A total of 15 amino acid variants in primary and second‐sphere residues were produced and characterized in terms of their copper binding and redox properties. PfCopC has a very high affinity for Cu(II) and also binds Cu(I). A high reorganization barrier likely prevents redox cycling and, thus, catalysis. In contrast, mutations in the conserved second‐sphere Glu27 enable slow oxidation of ascorbate. The crystal structure of the variant E27A confirmed copper binding at the His‐brace. Unexpectedly, Asp83 at the equatorial position was shown to be indispensable for Cu(II) binding in the His‐brace of PfCopC. A PfCopC mutant that was designed to mimic the His‐brace from lytic polysaccharide monooxygenase‐like family X325 did not bind Cu(II), but was still able to bind Cu(I). These results highlight the importance of the proteinaceous environment around the copper His‐brace for reactivity and, thus, the difference between enzyme and chaperone. Abstract :